BUSINESS MODEL CANVAS SEBAGAI MEDIA PENGGALIAN POTENSI DESA DAN PENILAIAN KELAYAKAN USAHA BUMDES - Sunaryono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
Villages in Indonesia generally have natural resources that can be one of the potentials that can be developed and can improve the economy of the village community. Lack of human resource capacity in the village makes these various natural resources cannot be managed properly. Because of this the village ministry has made a regulation that requires BUMDes in every village and may get initial funding from the Village Fund which is the transfer of funds from the center directly to the village. And with the presence of BUMDes, it is hoped that it can explore the potential of the village and help encourage economic growth in the village, and as a tool to explore the potential of the village is designed a media called the